Implementation of Virtual Try-On Product to Enhance Customer Satisfaction - Dawis, Aisyah Mutia; Ardhani, Rahmad; Setiyanto, Sigit; Khasanah, Aulia Uswatun; Muqorobbin; Tantra, Handoko (Publisher: Fakultas Ilmu Komputer, Institution: Universitas Lancang Kuning, 2024)
In the digital age, customer experience is key to business success. Augmented Reality (AR) technology offers immense potential to enhance the shopping experience, particularly through virtual try-on features. This research aimed to analyze the impact of implementing AR Product, specifically the virtual try-on feature, on customer satisfaction at PT Dua Naga Kosmetindo. The study employed the System Development Life Cycle (SDLC) waterfall model to develop and implement the virtual try-on feature on the E-Colux website. Black Box testing and User Acceptance Testing (UAT) were conducted to assess the success of the implementation and user acceptance levels. Black Box testing revealed a 100% success rate, while UAT yielded an average score of 87.7%. The results indicated a significant positive correlation between the use of virtual try-on and customer satisfaction, particularly in the dimension of product satisfaction (86%-95%). Female respondents and younger generations exhibited higher satisfaction levels. This research demonstrates that the implementation of virtual try-on can significantly enhance customer satisfaction. However, further research with a larger and more diverse sample is needed to generalize these findings. Additionally, studies on the long-term impact of virtual try-on on customer loyalty and business performance are warranted.